Glow flow ionization mass spectrometry of small molecules. A comparison of a glow flow ionization source (‘GlowFlow’) with electrospray ionization and atmospheric pressure chemical ionization - Rhodri Owen (Rapid Communications in Mass Spectrometry, 2022)
RationaleIonization by atmospheric pressure gas discharge has been employed for a long time in mass spectrometry. Inductively coupled plasma mass spectrometry is an exemplar, and widely used for elemental analysis. The technique has less uptake in organic mass spectrometry. We describe a simple source design that can be readily implemented in most atmospheric pressure ionization (API) systems and compare its performance with that of electrospray ionization (ESI) and atmospheric pressure chemical ionization (APCI).MethodsAn in-house designed helium gas discharge source (referred to as ‘GlowFlow’) was used on a Xevo G2-S time-of-flight mass spectrometer. The GlowFlow source was transferred to a compatible Xevo TQ-S triple-quadrupole mass spectrometer using an ultrahigh-performance liquid chromatograph inlet. Its performance was compared to that of Waters ESI and APCI sources.ResultsPreliminary results of GlowFlow on the Swansea instrument are presented to establish context and include analysis of low-molecular-mass polymers, benzoic acid and cinnamic acid. Comparison of performance on the Xevo TQ-S triple-quadrupole mass spectrometer involved three test mixtures. The method limits of detection (six-mix) for positive-ion GlowFlow source were between 0.03 and 10.00 pg with good linear response over two to four orders of magnitude and values of R2 > 0.98. The GlowFlow ionization source provided a signal intensity that was an order of magnitude greater than that of ESI for an atmospheric pressure gas chromatography standard mix and ionized several compounds that ESI could not.ConclusionsThe current GlowFlow design is relatively simple to retrofit to most API systems due to its small size. The sensitivity of the GlowFlow design is typically an order of magnitude less than that of ESI in positive-ion mode, but similar in sensitivity in negative-ion mode and comparable to that of APCI.